STUDI LITERATUR TENTANG EFEKTIVITAS MODEL PEMBELAJARAN BERBASIS PERMAINAN DALAM MENINGKATKAN KEBUGARAN JASMANI SISWA SEKOLAH DASAR - Ely Yuliawan; Ade Kurniawan Triwahyuda; Triyo Nova Utomo; Regina Ingrasias Sidabutar; Ahmad Maulana Ahsan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the effectiveness of game-based learning models in improving the physical fitness of elementary school students through a literature review of ten national journals published between 2021 and 2025. The research employed a literature study approach by analyzing empirical findings from previous studies. The results indicate that game-based learning consistently enhances various components of physical fitness, including endurance, speed, agility, and muscular strength. In addition to improving physical fitness, this model also increases students’ motivation, participation, and social interaction during physical education learning activities. Another strength of this model lies in its flexibility, allowing it to be adapted to different school environments and available facilities. Overall, game-based learning is an effective and recommended strategy for optimizing elementary students’ physical fitness within the context of physical education.